2005
DOI: 10.1111/j.1532-7795.2005.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trends in Adolescent Suicidal Ideation

Abstract: Research using retrospective or cross-sectional data suggests that suicidal ideation rates peak during mid-adolescence. This study used a longitudinal, community sample of adolescents who reported suicidal ideation repeatedly over 7 years to examine suicidal ideation trends. We hypothesized that a mid-adolescence peak in ideation is limited to adolescents exposed to friends' or family members' suicidality. Ideation trends were compared across groups exposed and not exposed to others' suicidality and statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
7
26
5
1
Order By: Relevance
“…Specifically, youth in the externalizing class were more likely to be younger; the internalizing class was more likely to be older and females; and the delinquent class was more likely to be older and males (Leve et al., ; Zahn‐Waxler et al., ). However, there were also inconsistencies with previous findings such as the youth in the parent‐reported high‐risk classes were more likely to be younger, whereas, previous findings have shown that suicidal ideation peaks during mid‐adolescence (Rueter & Kwon, ).…”
Section: Discussioncontrasting
confidence: 76%
“…Specifically, youth in the externalizing class were more likely to be younger; the internalizing class was more likely to be older and females; and the delinquent class was more likely to be older and males (Leve et al., ; Zahn‐Waxler et al., ). However, there were also inconsistencies with previous findings such as the youth in the parent‐reported high‐risk classes were more likely to be younger, whereas, previous findings have shown that suicidal ideation peaks during mid‐adolescence (Rueter & Kwon, ).…”
Section: Discussioncontrasting
confidence: 76%
“…According to Rueter and Kwon, a higher mean age in a sample of adolescents may influence prevalence results since suicide ideation rates increase with age. 17 Although this study has several strengths, it also has some limitations. Although Kovacs, 18 the original author of CDI, recommended that scores 1 and 2 of item 9 should be considered as an endorsement of suicidal ideation, and previous studies with adolescents with similar objectives have used them, 19,20 the measure of suicidal ideation in our study was based on just one question of a depressive scale.…”
Section: Discussionmentioning
confidence: 98%
“…However, the predictive value of commonly used risk factors for suicide is hindered by the fact that none of them are pathognomonic. Adolescence is a period during which many individuals will exhibit suicidal ideation [9] without necessarily posing a clinical threat.…”
Section: Introductionmentioning
confidence: 99%